Karakter Pertumbuhan Bawang Merah (Allium ascalonicum L.) Varietas Lokal Samosir Pada Beberapa Dosis Iradiasi Sinar Gamma - Afifa Ulfa Batubara; Mariati Mariati; Ferry Ezra T. Sitepu (Universitas Sumatera Utara, 2015)
The aim of the research was to identify growth characters of shallot var. local samosir with gammarays irradiation. Research was conducted at the Jl. Selamet Ketaren, Medan with a height of 25meter above sea level began from April until July 2014. Bulbs of shallot were exposed to severaldoses (0, 1, 2, 3, 4, 5, and 6 Gy) using Co60 source. Differencies of growth characters (shoot length,leaf number and tiller number per clump, harvest time, fresh and dry weight of bulb per plant, bulbdiameter and average weight per bulb) was analyze by t test using minitab v.16. The results showedshoot length 6 weeks after planting (WAP) were shorter 1.97cm, 2.38cm, 3.1cm, 4.73cm and4.49cm at doses 2,3,4,5,6 Gy; leaf number 2 WAP were reduced 35.16% and 39.24% at dose 5 and6 Gy, meanwhile tiller number 6 WAP was increased 13.88% at dose 6 Gy respectively comparedto control. Fresh weight and dry weight of bulb were lighter 30,39% and 37,04% at doses 5 Gy and38,52% and 47,44% at doses 6 Gy; average weight per bulb were lighter 23,2%, 47,64% and47,98% and bulb diameter were smaller 11,48%, 25,48% and 30,41% at doses 4,5,6 Gy respectivelycompared to control.Key words : Shallot var samosir, gamma rays irradiation, doses